Development of an online music teaching platform - Cappellozza, Alexandre; Davi Chaves Rosa, Abner (Práticas em Contabilidade e Gestão, 2026)
T his study presents a solution to an opportunity for creating a technological artifact to develop an Online Music Teaching Platform (PLIM) in a music school in Brazil. The study demonstrates the development of a new approach to consuming musical educational content, as well as an initiative to explore the potential of a business opportunity for creating a music education streaming platform. This article adopts the methodological principles of the Design Science Research approach for the development of this technological artifact. In addition to the initial development of the platform and the implementa tion stage carried out in this work, the pilot project enabled us to understand the perceptions of those interested in developing musical skills, the effectiveness of the content created, and adherence to the musical educational model proposed by the company.